2001
DOI: 10.1017/s1047951101000324
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in levels of triidothyronine following the first stage of the Norwood reconstruction for hypoplastic left heart syndrome

Abstract: The data demonstrate significant decreases in levels of free and total triiodothyronine during the early postoperative period. These changes in levels of thyroid hormone may have adverse effects on cardiac function during this phase of recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The TSH recovered back to preoperative levels by POD 4 with a possible rise above preoperative levels starting on POD 7. FT4 and arguably RT3 both recovered to preoperative levels, but TT3, FT3I, and T3U showed no evidence of recovery by POD 7. Several smaller studies in children undergoing cardiac surgery similarly showed the presence of NTIS [33,[47][48][49][50][51][52][53][54][55][56][57]. As mentioned previously, Zucker et al [33] followed 27 children of which 18 underwent cardiac surgery.…”
Section: Ntis In Childrenmentioning
confidence: 86%
See 1 more Smart Citation
“…The TSH recovered back to preoperative levels by POD 4 with a possible rise above preoperative levels starting on POD 7. FT4 and arguably RT3 both recovered to preoperative levels, but TT3, FT3I, and T3U showed no evidence of recovery by POD 7. Several smaller studies in children undergoing cardiac surgery similarly showed the presence of NTIS [33,[47][48][49][50][51][52][53][54][55][56][57]. As mentioned previously, Zucker et al [33] followed 27 children of which 18 underwent cardiac surgery.…”
Section: Ntis In Childrenmentioning
confidence: 86%
“…In other studies, Mainwaring has attempted to differentiate a thyroid response among the various types of congenital cardiac malformations. In one study, he followed the thyroid function in 14 newborns, aged 1-12 days old, all with hypoplastic left heart syndrome undergoing first stage Norwood reconstruction [52]. These children all had decreases in FT3 and TT3 levels starting with the initiation of CPB and reaching a nadir at 24 h after surgery.…”
Section: Ntis In Childrenmentioning
confidence: 99%
“…In addition, the T3 infusion was associated with a reduced need for postoperative intensive care (6). Studies have also found a significant decrease in the levels of free and total T3 in the postoperative period following stage 1 reconstruction for hypoplastic left heart syndrome (19) and the Fontan procedure (20). T3 supplementation has also been shown to increase heart rate without concomitant decrease in systemic blood pressure in infants after cardiopulmonary bypass, suggesting that repletion improves myocardial oxygen consumption (7).…”
Section: Discussionmentioning
confidence: 99%
“…After CPB, serum thyroid hormone levels are depressed (100). Because of the known effects of thyroid hormone on ventricular function, several studies have evaluated the role of thyroid replacement therapy in children after cardiac surgery (101)(102)(103)(104).…”
Section: Other Strategies For Improving Circulatory Functionmentioning
confidence: 99%